let x be object ; :: thesis: for G being non empty multMagma
for A being Subset of G
for g being Element of G holds
( x in g * A iff ex h being Element of G st
( x = g * h & h in A ) )

let G be non empty multMagma ; :: thesis: for A being Subset of G
for g being Element of G holds
( x in g * A iff ex h being Element of G st
( x = g * h & h in A ) )

let A be Subset of G; :: thesis: for g being Element of G holds
( x in g * A iff ex h being Element of G st
( x = g * h & h in A ) )

let g be Element of G; :: thesis: ( x in g * A iff ex h being Element of G st
( x = g * h & h in A ) )

thus ( x in g * A implies ex h being Element of G st
( x = g * h & h in A ) ) :: thesis: ( ex h being Element of G st
( x = g * h & h in A ) implies x in g * A )
proof
assume x in g * A ; :: thesis: ex h being Element of G st
( x = g * h & h in A )

then consider g1, g2 being Element of G such that
A1: x = g1 * g2 and
A2: g1 in {g} and
A3: g2 in A ;
g1 = g by ;
hence ex h being Element of G st
( x = g * h & h in A ) by A1, A3; :: thesis: verum
end;
given h being Element of G such that A4: ( x = g * h & h in A ) ; :: thesis: x in g * A
g in {g} by TARSKI:def 1;
hence x in g * A by A4; :: thesis: verum